Android Application Development for Force Topics in Year Six (6) Science Subject - Hamzah, Norhasyimah; Collin, Carolina; Zakaria, Normah; Ariffin, Arihasnida; Rubani, Siti Nur Kamariah (Research and Innovation in Technical and Vocational Education and Training, 2022)
Android learning applications have become a necessity nowadays where students use them as an additional learning medium. This study aims to develop a learning android application for the topic of force in the subject of Science Year Six (6). This study uses the ADDIE model as a guide in the development of android applications for force topics in science subject Year six. The ADDIE model involves five (5) phases, namely the analysis phase, design phase, development phase, implementation phase, and evaluation phase. In the analysis phase, the developer analyzes the hardware and software requirements required for the development of learning application products. During the design phase, the developer designs the storyboard based on three (3) designs, namely content design, interface, and interaction. Development phase, developers develop learning android application products using software such as Adobe Animate CC, Adobe Flash CS6, Adobe Photoshop 2018, Adobe Illustrator CC, and Audacity. The implementation phase allows the developer to upload the apps to the Play store. Finally, the evaluation phase involves the evaluation of the level of functionality of the product by three (3) experts. The findings from the expert evaluation showed that all three experts agreed that the functionality of the product worked well and was appropriate for the age of the user. In conclusion, this product can be one of the teaching aids to enable students to understand the topic of force for science subjects in year six (6) better.